Design of nematic liquid crystals to control microscale dynamics. Issue 2 (2nd July 2020) - Lavrentovich, Oleg D.
ABSTRACT: Dynamics of small particles, both living and inanimate, has fascinated scientists for centuries. Learning how to control it could open technological opportunities in the transformation of stored or environmental energy into systematic motion. This review presents an approach to command microscale dynamics by using liquid crystals as an environment and liquid crystal elastomers as substrates. The orientational order of liquid crystals and associated properties, such as elasticity, surface anchoring, and bulk anisotropy, enable new dynamic effects, ranging from the propagation of particle-like solitary waves to steady directional self-locomotion of active droplets.  Liquid crystals could be photoaligned into patterns with varying molecular orientations.  In the presence of an electric field, these patterns transport solid and fluid particles by nonlinear electrokinetics rooted in anisotropy of conductivity and permittivity. Patterned lyotropic liquid crystal environment commands the dynamics of swimming bacteria by mediating their hydrodynamic interactions, rectifying active flows, and producing collective polar modes of swimming. Patterned elastomer coatings demonstrate a pre-programmed topography that is effective in shaping the morphology of living tissues. The liquid-crystal guidance holds a major promise in achieving the goal of commanding microscale active flows.